Review on computational modeling for the property, process, product and performance (PPPP) characteristics of additively manufactured porous magnesium implants - Ramsha Imran (12431698) (2022)
Recently, magnesium (Mg) and its alloys are gaining the attention of researchers as these materials can provide mechanical properties comparable to natural bone. Additive manufacturing (AM) techniques have also evolved in the biomedical sector owing to their precision in fabricating desired parts with varying shapes, intricacy, and porosity required for implant functionality. With increasing interest in AM of Mg-based biomedical implants, there is a pressing need to understand existing accomplishments, state-of-the-art materials, and fabrication technology and to identify remaining research gaps through a comprehensive literature review existing in this field and highlight hindrances and challenges associated. In this review study, a particular focus is placed on understanding computational modeling techniques employed for the design, manufacturing, and performance analysis of AM porous scaffolds. Therefore, progress in material synthesis and associated challenges are reviewed in this study, and conclusions and future research recommendations are drawn based on reviewed literature. This review study concludes that there is an unmet need to develop accurate, fast, and inexpensive computational modeling for AM of Mg-based implants to increase predictability capacity and capabilities of material synthesis, fabrication, and resulting product property and performance. Other Information Published in: Bioprinting License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bprint.2022.e00236